« Je parle du française, où ? » Interlangue française d'un germanophone Étude longitudinale du lexique - Khatra, Simrit (Studien des Interdisziplinären Frankreich-Schwerpunkts der Universität Innsbruck, 2013)
How to talk when you learn a foreign language? The language of the learner does not match from the beginning of the target language, it is characterized by numerous "errors" that are partially pre-programmed by the interference of the mother tongue. This language can be used as interlangue (Lerner Language) - a language between the target language and the mother tongue - are referred to. Empirical research on learner language are still not very present in linguistics, especially in the area of ​​lexis. The theme of this work is the presentation of the development of interlangue a germano-speaking Austrian student during his four years of learning French as a foreign language.